Quality of Life in Modern Times (Journal of Universal Excellence, 2026)
Research question (RQ): How does modern times affect the quality of life according to individual indicators?Purpose: The purpose is to present an individual quality of life indicator and provide an assessment of the comparison of Slovenian and EU statistics and our research.Method: The qualitative method was used in the research, where the analysis of various articles and literature was carried out.Results: Compared to the past, the quality of life decreases, the help of people, the desire for progress, the desire for a better, higher quality life are lost.Organization: Adequate quality of life can enable better conditions and greater interest in the positive life of modern times.Society: Individuals are those who, with their satisfied, positive thinking and efforts, can guide and set goals for a quality future of life.Originality: Presenting an overview of the quality of life in modern times.Limitations/further research: Research was done based on articles and literature.
Keywords: quality of life; modern times; people; time; security; material goods; relationships; people's help